Determining the Priority Strategy in the Implementation of E-Government Through SWOT Analysis Model - Karyono, Otong; Agustina, Kania (Budapest International Research and Critics University, 2019)
The implementation of technology and information in the government environment or Electronic Government (E-Government) is a very important factor to be carried out by the government in order to implement more responsive, transparent, accountable services to realize a more quality service system in responding to the challenges of technological development today. Thus, the government, society, and business parties can access information and transact quickly, precisely and cheaply. Therefore, the strategy formulation is indispensable in responding to challenges and weaknesses to maximize strengths and opportunities. The strategy formulation that is considered relevant for conducting this present research is the SWOT analysis. This research uses a descriptive qualitative research model by identifying strengths, weaknesses, opportunities, and threats through research questionnaires and interviews conducted on 30 employees involved in the process of public service activities. Technique for analyzing internal and external business environments uses SWOT. The results show that by considering the strengths and weaknesses as well as external factors to take into account the opportunities and threats, it can be seen that the appropriate strategies to realize the implementation of E-Government to achieve quality service is the aggressive strategy, which refers to the strategy of development regarding very good situations because there are strengths to be utilized to seize profitable opportunities.